1983
DOI: 10.1002/cjce.5450610604
|View full text |Cite
|
Sign up to set email alerts
|

Heat and mass transfer in non‐newtonian fluid flow with power function velocity profiles

Abstract: Heat and mass transfer in laminar and turbulent non‐Newtonian fluids is investigated in this work using the power function velocity profiles. Analytical solutions are presented for cases of mass transfer in laminar non‐Newtonian fluid flows, namely for a flat velocity profile (plug flow), for the case of a constant velocity gradient at the solid boundary (Couette flow), and for the velocity distribution within a laminar boundary layer on a flat plate, and these are illustrated by rotating disks and cylinders i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 45 publications
(44 reference statements)
1
2
0
Order By: Relevance
“…(11) indicates that k L increases with increasing E as well as eq. (22). Recently, Figueiredo and Calderbank' found that the values of k, are proportional to and concluded that k , is dependent on the turbulent intensity expressed as a function of E. This is consistent with the present work.…”
Section: Resultssupporting
confidence: 93%
“…(11) indicates that k L increases with increasing E as well as eq. (22). Recently, Figueiredo and Calderbank' found that the values of k, are proportional to and concluded that k , is dependent on the turbulent intensity expressed as a function of E. This is consistent with the present work.…”
Section: Resultssupporting
confidence: 93%
“…Most of the studies [13,14] concentrated only on the heat transfer to blood flowing through the arteries but limited attentions have focused to study the mass transfer processes (cf. [15,16]). There might be so many reasons on tackling blood flow in problems in the presence of mass transfer.…”
Section: Introductionmentioning
confidence: 96%
“…In the recent past, the study of the combined effects of heat and mass transfer on biofluids has become quite interesting to many researchers both from the theoretical and experimental or clinical point of view (Chakravarty and Sen, 2005;Eldabe et al, 2007;Nadeem and Akbar, 2009). Most of the studies concentrated only on the heat transfer (Khanafer et al, 2007;Ogulu and Abbey, 2005) to blood flowing through the arteries but limited attentions have been focused to study the mass transport processes (Kawase and Ulbrecht, 1983;Valencia and Villanueva, 2006). There might be so many reasons on tackling blood flow in problems the presence of mass transfer.…”
Section: Introductionmentioning
confidence: 98%